A Proposal for Developing the Textbook of Hadith and Islamic Education for First Grade in Secondary Schools in Saudi Arabia - Alatwi, Fahad Odeh Awad; Qutb, Iman Mohamed Mabrouk (Journal of Curriculum and Teaching Methodology, 2024)
This study aimed to identify A Proposal for the development of the textbook of Hadith and Islamic Education (1) for the first grade in secondary school in Saudi Arabia in the light of life skills. In order to do that, The purpose of the study tool, in which life skills were classified into seven main skills: (problem solving and decision-making, interpersonal relations and ethics, coexistence with reality, creative thinking, critical thinking, communication and self-learning).The study confirmed validity and stability of the tool. The study concluded the following results: The most occurrences sub-skills were as following: in problem-solving and decision-making skills was the skill of identifying the problem and its causes, with (9) duplicates, in interpersonal relations and ethics skills was the skill of imitating the Prophet's morals, with (5) duplicates, in coexistence with reality skills was self-control skill with (3) duplicates, in creative thinking skills was brainstorming skill with (12) duplicates, in critical thinking skills was analyzing the topic skill, with (12) duplicates, in communication skills was the skill of conveying information with (18) duplicates, in self-learning skills were the sub-skills: (identifying strengths and weaknesses; taking responsibility; motivation; self-evaluation), with (2) duplicates. The study recommended as the following: Including the low or non-repeated skills in the textbook of Hadith and Islamic education, Conducting further researches and studies on Islamic education courses at all academic levels and Holding educational courses in planning and teaching methods to develop students' life skills.
Keywords: Hadith; Islamic Education; Life Skills; Problem Solving; Decision Making; Saudi Arabia; Curriculum Development